A Digital Encyclopedia â€œPerjalanan Joko Toleâ€: Fulfill Recreation Rights for Children in Bangkalan - Eka Oktavianingsih; Siti Fadjryana Fitroh; Ria Kusuma Wardani (JPPM (Jurnal Pendidikan dan Pemberdayaan Masyarakat), 2023)
Problems related to fulfilling childrenâ€™s rights, including early childhood recreation rights, continue to exist. However, sometimes parents and teachers think childrenâ€™s right to recreation is less critical because it is only for fun. In contrast, it impacts childrenâ€™s social-emotional aspects, such as emotional regulation and self-confidence. On the other hand, Bangkalan Regency itself has many local tours. The aims of this study were: (1) to develop a digital encyclopedia containing local tourism and (2) to test the feasibility of a digital encyclopedia in terms of validity and practicality. The researcher involved 39 kindergarten-aged children at TK Kartika IV-89 Bangkalan as the sample. This study was research and development with ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model. Data collection techniques consisted of interviews, questionnaires, observation, and documentation. Research data were analyzed quantitatively and qualitatively to review whether the digital encyclopedia media developed for local tourism met the criteria of validity and practicality.Â